Developing Needs Assessment Instrument On The Topic Of Classroom Guidance In Social Guidance And Counseling - Nindya Ayu Pristanti; Muh Farozin (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2018)
This study aimed to know the psychometry characteristic of need assessment instrument on the topic of classroom guidance in the social guidance and counseling services for students at SMP Negeri 1 Yogyakarta. This study was research and development followed Saifuddin Azwar model. Data collection method was a rating scale. Data analysis used content validity which was formulated by Aiken, construct validity used Exploratory Factor Analysis (EFA) and reliability analysis used Alpha Cronbach. The results of this development research were the need assessment instrument on the topic of classroom guidance in social guidance and counseling services for students at SMP N 1 Yogyakarta based on the content validity obtained 0,85, reliability 0,98 and found several new item groups from exploratory factor analysis result. It could be concluded that instrument of need assessment on the topic of social guidance and counseling was feasible to use